Salient Customer Relationship Management (CRM) dimensions contributing to customer loyalty for UEMS in facility management / Al Ashraf Zarif Al Bakri, Nurul Azrina Rusni & Ezuana Jaaffar - Al Bakri, Al Ashraf Zarif; Rusni, Nurul Azrina; Jaaffar, Ezuana (2018)
Growing revenues and profits are the most prominent business objectives of many facility management providers which ultimately help to strengthen the company’s presence in the industry. Focusing on managing relationship with customers can cultivate loyalty which subsequently lead to customer retention. The purpose of this study is to establish salient Customer Relationship Management (CRM) dimensions contributing to customer loyalty in Facilities Management. An in-depth research was pursued to ascertain the influence of the CRM dimensions (customer orientation customer knowledge, customer empowerment and complaint resolution) towards customer’s loyalty for UEMS. The data were analysed from 77 questionnaires received from UEMS customers located in Selangor, Perak, Kuala Lumpur, N. Sembilan, Malacca, Johor and Penang. Result for the regression analysis revealed that CRM played a major role towards customer loyalty with both customer knowledge and customer orientation being the two dimensions of CRM with provided the significant impact. Within the context of Facilities Management industry in Malaysia, the results gave evidence that focusing on the two CRM dimensions will lead to customer loyalty which UEMS can take advantage upon to further strengthen its business growth in the industry. Recommendations were given for UEMS to develop comprehensive training program to all level of staff to further enhance customer-oriented culture in the organization and also to utilized software-based CRM to manage customer knowledge and information in an efficient manner as the company continue to grow its business.